Education for Life: A qualitative study on Adolescents’ perspectives on health - parvizi, soroor; ahmadi, fazllolahe (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Adolescence is a period of transience and development from childhood to adulthood and they face risky behaviors. This study aimed to describe and explain the educational predisposing factors on adolescents’ health.